Prevalence of Short Stature in Four-to-Six-Year-Old Children and Its Influencing Factors in the North East of Iran - Jaefarian1, Sussan; Chaman2, Reza; Amiri3, Mohammad; Khosravi4, Ahmad; Sangchooli Moghadam5, Mansoureh; Ghari6, Arefeh; Haratipour7*, Hosein (Shahroud Journal of Medical Sciences, 2017)
Background: Growth pattern in children is one of the most important indicators of public health. This study aimed to determine the prevalence of short stature in children and its influencing factors in Shahroud, northeast of Iran.Methods: In this cross-sectional study, 700 four-to-six year-old children were selected in 2015 through stratified random sampling. First, a list of preschools and kindergartens was prepared and samples were selected from 20 kindergartens and preschools. After coordination with parents and obtaining their respective consent, heights and weights of children were measured. Children with short stature were followed up with further diagnostic tests, including hormonal and biochemical tests, and their bone age was determined.Results: In this study, there were 378 (54.2%) girls and 322 (45.8%) boys. The prevalence of short stature was 2.3%. In 74.9% of cases, short stature was due to pathological causes, and in 25.1% it was due to natural and familial factors. The results showed that anemia and insulin-like growth factor 1 (IGF1)-related disorders were the most frequent underlying causes of short stature in children. There were significant relationships between short stature at birth (P=0.001), positive history of mother’s short stature (P=0.004), and children’s physical activity (P=0.029), but no significant relationship was observed between short stature and gender, birth weight, children’s living with parents and family’s economic status (P≥0.05).Conclusions: Birth height, mother’s short stature and physical inactivity are risk factors identified in this study which can influence short stature of four-to-six-year-old children.